KADAR TESTOSTERON TIKUS PUTIH (Rattus norvegicus L) SETELAH MENGKONSUMSI BUAH TERONG TUKAK (Solanum torvum Sw) - Kaspul Kaspul (Bioscientiae, 2007)
A study has been made to confirm the traditional belief that pea eggplant could affect male fertility. Pea eggplants contain solasodine that might reduce testosterone in male human and other vertebrate reproductive system, but the effect pea eggplant on testosterone concentration is not clear. The experiment was conducted to assess the effect of pea eggplant on testosterone concentration in rats. Forty three-month-old male rats were daily fed with four food groups: (1) 15 g of standard food as control, (2) 10 g of standard food plus 5 g pea eggplant, (3) 5 g of standard food plus 10 g pea eggplant, and (4) 15 g pea eggplant. After one month testosterone concentration was determined by radioimmunoassay. There seemed to be a decrease in testosterone with increasing pea eggplant consumption, but statistical analysis showed insignificant difference in testosterone concentration among treatments, indicating that  testosterone in rats was not significantly affected by pea eggplant.